2022
DOI: 10.1152/ajpheart.00461.2021
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of thermoneutral housing conditions on murine cardiometabolic function

Abstract: Mouse models are used to model human diseases and perform pharmacological efficacy testing to advance therapies to humans; most of these studies are conducted in room temperature conditions. At room temperature (22°C), mice are cold stressed and must utilize brown adipose tissue (BAT) to maintain body temperature. This cold stress increases catecholamine tone to maintain adipocyte lipid release via lipolysis, which will fuel adaptive thermogenesis. Maintaining rodents at thermoneutral temperatures (28°C) ameli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Before the initiation of DOCA-salt treatment, housing at TN alone resulted in expected reductions in BP and HR, as sympathetic stimulation of HR is withdrawn as mice move to TN housing. 7–9 Interestingly, although HR reductions in response to chlorisondamine were abolished by housing at TN, BP reductions were similar to mice housed at RT. These data reinforce the concept that TN housing selectively reduces autonomic stimulation of the heart 8,9 but perhaps not the vasculature.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Before the initiation of DOCA-salt treatment, housing at TN alone resulted in expected reductions in BP and HR, as sympathetic stimulation of HR is withdrawn as mice move to TN housing. 7–9 Interestingly, although HR reductions in response to chlorisondamine were abolished by housing at TN, BP reductions were similar to mice housed at RT. These data reinforce the concept that TN housing selectively reduces autonomic stimulation of the heart 8,9 but perhaps not the vasculature.…”
Section: Discussionmentioning
confidence: 93%
“…28 Unfortunately, such documenting and appreciating the impact of environmental variables (such as ambient temperature) upon cardiovascular physiology in both humans and rodent models lags behind efforts to incorporate these factors into studies of bioenergetics and obesity. 1,2,29,30 Recent studies have highlighted the impact of ambient temperature upon cardiovascular functions in mice, [7][8][9] but there remains a general lack of appreciation for the complex interactions among ambient temperature and cardiometabolic stimuli upon fluid and electrolyte balance, energy homeostasis, and BP control in experimental models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermoneutral housing alters many, but not all, metabolic responses ( 67 70 ). Regarding bone, compared to room temperature, thermoneutral housing prevents premature cancellous bone loss, attenuates risperidone-induced trabecular bone loss, has modest effects on cortical response to mechanical loading, and does not impact polyethylene-particle induced osteolysis ( 46 , 71 , 72 ).…”
Section: Discussionmentioning
confidence: 99%
“…Of relevance, female mice are highly resistant to obesity-induced nonalcoholic fatty liver disease and subsequent steatohepatitis, but this resistance is extinguished if the mice are housed at thermoneutrality ( 296 ). More recently, studies in male mice housed at either room temperature or thermoneutrality have demonstrated that thermoneutrality lowers heart rate and mean arterial pressures in lean mice, whereas these actions are blunted in mice subjected to high-fat diet-induced obesity ( 252 ). Taken together, as the field continues to collaborate and refine the current models of diabetes, while also developing new models, this should result in further improvements in our ability to clinically manage diabetes-related cardiovascular disease.…”
Section: Final Summary and Important Considerations For The Futurementioning
confidence: 99%